Prevalence of Common Dental Problems among Primary School Children in a Rural Area of Mymensingh (Journal of Dentistry and Allied Science, 2025)
Introduction: In Bangladesh little is known about the prevalence of dental problems, hygiene practices and dietary factors among school age children. Methods: This cross-sectional study was conducted at Ramganj Govt. Primary School, Mymensingh, Bangladesh from June 2022 to May 2023. A total of 79 students were included in the study. The sampling procedure was a purposive sampling. To collect required information personal interview was taken by using a pre-tested questionnaire & dental condition was examined. The collected data were analyzed using SPSS version 20.0. Results: In this study, among 79 students which 47 (58.49%) had tooth problems: 34 dental caries (43.04%), 9 gingivitis (11.39%), 6 dental abscess (7.59%), 10 dental calculus (12.66%), and 1 had periodontal inflammation (1.27%). The problems were overlapping. Tooth-brushing 96-20%, daily bathing 94-94%, hand-washing after defecation were 96-20%, hand-washing before meal 98-73%. Most of them brush once and that is before breakfast. 36.71% consume balanced food. Consumption of calcium, Vitamin D precursors and Vitamin C rich foods were mostly acceptable. Conclusion: Important problems are dental caries and dental calculus. Improvement requires health education, dental care and raising awareness among children. More surveys are needed.Journal of Dentistry and Allied Science, Vol. 8 No 1: 34-42